2012
DOI: 10.1111/j.1445-5994.2012.02821.x
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin plus etoposide versus other platin‐based regimens for patients with extensive small‐cell lung cancer: a systematic review and meta‐analysis of randomised, controlled trials

Abstract: There is no strong evidence that any clinical advantage for extensive small-cell lung carcinoma patients requiring chemotherapy when comparing EP with other platin-based regimens, with exception of IP that might prolong overall survival. The decision to prescribe which chemotherapy should take into consideration both cost and treatment preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…Data from our analysis indicate that there is insufficient evidence to prove the superiority of EP/CP over other multidrug protocols. This negative result is similar to the parallel data from Jiang et al ., who compared the efficacy of EP with other platin‐based regimens in patients with small‐cell lung carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…Data from our analysis indicate that there is insufficient evidence to prove the superiority of EP/CP over other multidrug protocols. This negative result is similar to the parallel data from Jiang et al ., who compared the efficacy of EP with other platin‐based regimens in patients with small‐cell lung carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…To improve the chemotherapeutic efficacy and overcome chemoresistance, several studies have explored the incorporation of novel agents and creation of new regimens. Unfortunately, there is no strong evidence that other platinum-based regimens have any clinical advantage over EP [15]. Jiang et al reported that irinotecan/cisplatin might improve OS with overall HR of 0.87 (P = 0.01), but they could not detect a significant effect of irinotecan/cisplatin versus EP on survival (P = 0.12) after exclusion of a Japanese trial [16] due to heterogeneity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no strong evidence that other platinum-based regimens have any clinical advantage over EP [15]. Jiang et al reported that irinotecan/cisplatin might improve OS with overall HR of 0.87 (P = 0.01), but they could not detect a significant effect of irinotecan/cisplatin versus EP on survival (P = 0.12) after exclusion of a Japanese trial [16] due to heterogeneity [15]. Lee et al [17] reported that gemcitabine/carboplatin did not improve survival benefits, but did increase grade 3/4 hematological toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term survival in SCLC patients has not been satisfactory (3)(4)(5). Etoposide plus platinum (EP) is currently the standard first-line treatment used in SCLC to obtain longer overall survival (OS) and progression-free survival, although numerous chemotherapeutic regimens comprising various drugs have been investigated and tested in clinical trials (6,7).…”
Section: Introductionmentioning
confidence: 99%